EFFECTIVE FORMS OF PHYSICAL EDUCATION AND SPORTS EVENTS IN EDUCATIONAL INSTITUTIONS (Scientific journal of the Fergana State University, 2024)
This article is aimed at physical development, rehabilitation and preparation of students for life, education of spiritually mature people in order to reveal effective forms of physical culture and sports activities in educational institutions. In addition, morning physical education classes, physical education classes, sports clubs, sports competitions and holidays, as well as tourist events held on weekends and holidays were highlighted